Do place of residence and ethnicity affect health services utilization? evidence from greece - Pappa Evelina; Lahana Eleni; Niakas Dimitris (BMC, 2011)
Abstract Background Equal utilization of health services for equal need, is one of the main targets for public health systems. Given the public-private structure of the Greek NHS, the main aim of the study was to investigate the impact of underlying factors, such as health care needs, socio-demographic characteristics and ethnicity, on the utilization of primary and hospital health care in an urban and rural population of the Greek region, Thessaly. Methods A cross-sectional study was carried out in 2006 in Thessaly, a Greek region of Central Greece, in a representative sample of 1372 individuals (18+ years old, response rate 91.4%) via face-to-face interview. Health care needs were determined by self-perceived health status estimated by the SF-36 Health Survey, using the summary scores of physical and mental health. The utilization of primary care was measured by last month visits to 1) primary public services and 2) private practitioners visits and utilization of secondary care was measured by past year visits to 3) public hospital emergency departments and 4) admissions to public hospitals. Multivariable stepwise logistic regression analysis was applied in the whole sample and separately for the urban and rural population, in order to determine the predictors of health services utilization. Statistical significance was determined with a p value < 0.05. Results Health care needs were the most significant determinants of primary and secondary health services utilization in both the urban and rural areas. Poor physical and mental health was associated with higher likelihood of use. In the urban areas middle-aged, elderly and Greeks were more likely to use primary health services, whereas primary education was associated with more visits to the emergency departments. Wealthier individuals were two times more likely to be admitted to hospitals. Individuals from the rural areas with university education visited more the public primary services, while wealthier individuals visited more the private practitioners. Immigrants had a higher likelihood of visiting emergency departments. Conclusions Although health care needs were the main determinant of health services utilization in both the urban and rural population, socio-economic and ethnic differences also seem to contribute to the inequities observed in some types of health services use, favouring the better-off. Such findings provide important information to policy makers, which attempt to reduce inequalities in health care according to place of residence and ethnicity.